Voluntary Disclosure and Ownership Structure Among Saudi Arabia Companies - Mgammal, Mahfoudh Hussein Hussein (2011)
This paper examines the effect of corporate governance characteristics (ownership structure) on the extent of voluntary disclosure in the financial reports among non-financial listed companies in Saudi Arabia. Currently, there is a growth in demands by stakeholders for companies to demonstrate greater transparency on their performance. However, few studies have been conducted in Saudi Arabia on the area of voluntary disclosure. The present study aimed to evaluate the current level of voluntary disclosure (VODSC) and investigate the influence of the variables, ownership structure (managerial ownership, family member on the board and government ownership level) and control variables (size, leverage and return on assets) in relationship to the level of voluntary disclosure in 2009 among 89 non-financial companies listed on the Saudi Stock Exchange. The results suggest that the corporate governance-related variables influence the level of information disclosed, thus confirming the hypotheses. The results showed that the level of voluntary disclosure (VODSC) level was acceptable compared to other studies. With regard to the quality of disclosure, my results on the corporate governance characteristics (ownership structure) showed that all the variables were significant positively linked to the level of voluntary disclosure extent (VODSC). Moreover, my results on the control variables (size, leverage and return on assets) indicate that there is significantly positive association with the level of voluntary disclosure extent (VODSC). The results of this study might be of interest to regulators, investment analysts, and market participants and can help Saudi authorities to enforce new policies toward improving the quality of financial reporting.